Lepiota elseae (Agaricales, Agaricaceae), a new species of section Lepiota from Spain - Caballero, Agustín; Vizzini, Alfredo; Muñoz, Guillermo; Contu, Marco; Ercole, Enrico (Phytotaxa, 2015)
A new species, Lepiota elseae, is described from Mediterranean areas in Spain in association with Quercus ilex, based on both morphological and molecular characters (analysis of the ITS-rDNA sequences). Illustrations of fresh basidiomata in situ and of the main macro- and micromorphological features are provided. L. elseae belongs to section Lepiota and is compared with morphologically similar taxa. The phylogenetic relationship with related species based on ITS sequences is discussed.